Natural metabolites from the soft coral Nephthea sp. as potential SARS-CoV-2 main protease inhibitors. Issue 11 (2nd June 2022) - Abdelhafez, Omnia Hesham; Fahim, John Refaat; Mustafa, Muhamad; AboulMagd, Asmaa M.; Desoukey, Samar Yehia; Hayallah, Alaa M.; Kamel, Mohamed Salah; Abdelmohsen, Usama Ramadan
Abstract: The ongoing spread of SARS-CoV-2 has created a growing need to develop effective antiviral treatments; therefore, this work was undertaken to delve into the natural metabolites of the Red Sea soft coral Nephthea sp. (family Nephtheidae) as a source of potential anti-COVID-19 agents. Overall, a total of 14 structurally diverse minor constituents were isolated and identified from the petroleum ether fraction of Nephthea sp. The characterised compounds were screened and compared for their inhibitory potential against SARS-CoV-2 main protease (M pro ) using Autodock Vina and MOE software. Interestingly, most compounds were able to bind effectively to the active site of M pro, of which nephthoside monoacetate ( 1) ; an acylated tetraprenyltoluquinol glycoside, exhibited the highest binding capacity in both software with comparable interaction energies to the ligand N3 and moderately acceptable drug-likeness properties, which drew attention to the relevance of marine-derived metabolites from Nephthea sp., particularly compound ( 1), to develop potential SARS-CoV-2 protease inhibitors. Graphical Abstract: UF0001